Doping-dependent nonlinear Meissner effect and spontaneous currents in high-Tc superconductors - Lee, S.-C.; Sullivan, M.; Ruchti, G.R.; Anlage, S.M.; Palmer, B.S.; Maiorov, B.; Osquiguil, E. (American Physical Society, 2005)
Fil: Maiorov, B. Comisión Nacional de Energía Atómica. Instituto Balseiro; Argentina; Los Alamos National Laboratory; Estados Unidos